Spodbujanje ustvarjalnosti in inovativnosti v bolnišnici X - Bogovič, Mateja (Revija za univerzalno odličnost, 2014)
Research Question (RQ) : Are creativity and innovation encouraged in Hospital X? Does satisfaction of employees at the workplace depend on the length of their employm ent? Does employee satisfaction depend on innovation? Purpose: It is important that creativity and innovation of employees are noticed in Hospital X in a timely manner. Various approaches can be used to motivate their creative thinking (using different pro fessional factors). Method: Qualitative method, questionnaire with 8 questions and processing of results with %2 test and frequency distribution. Results: The results of the research showed that 60% of employees at Hospital X were encouraged to be creative and innovative, whereas satisfaction at the workplace in connection with the period of employment did not have an effect on their satisfaction within the organization. Organization: The research results will give the management a clearer idea of employe es% opinions concerning their creativity and innovation. Society: Opinion of workers in a certain organization can encourage other organizations to be more creative and innovative. Originality: It is a small organization and results of the research refer to its originality. Limitations/Future Research : The limitation of this study was with regard to time and for this reason data collection was carried out only in the surgical unit of Hospital X
Keywords: approaches to encouragement; creativity; innovation; inovativnost; pristopi k spodbujanju; satisfaction of employees; ustvarjalnost; zadovoljstvo zaposlenih